2010
DOI: 10.1575/1912/3838
|View full text |Cite
|
Sign up to set email alerts
|

Biology and potential biogeochemical impacts of novel predatory flavobacteria

Abstract: Predatory bacteria are ubiquitous in aquatic environments and may be important players in the ecology and biogeochemistry of microbial communities. Three novel strains belonging to two genera of marine flavobacteria, Olleya and Tenacibaculum, were cultured from coastal sediments and found to be predatory on other bacteria on surfaces. Two published species of the genus Tenacibaculum were also observed to grow by lysis of prey bacteria, raising the possibility that predation may be a widespread lifestyle amongs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 210 publications
(107 reference statements)
1
2
0
Order By: Relevance
“…The absence of growth of strains isolates on agar-agar control and their growth on agar-agar in the presence of M. luteus confirmed the predation. All four selected Actinobacteria isolates showed ability to grow on different types of bacterial cells (Gram-positive, Gram-negative, and multidrug-resistant bacteria), demonstrating the lack of specificity of the predation process that requires the excretion of lytic enzymes, in line with previous reports for other predatory bacteria [44]. Most of these species also produced anti-microbial molecules on Bennett medium.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The absence of growth of strains isolates on agar-agar control and their growth on agar-agar in the presence of M. luteus confirmed the predation. All four selected Actinobacteria isolates showed ability to grow on different types of bacterial cells (Gram-positive, Gram-negative, and multidrug-resistant bacteria), demonstrating the lack of specificity of the predation process that requires the excretion of lytic enzymes, in line with previous reports for other predatory bacteria [44]. Most of these species also produced anti-microbial molecules on Bennett medium.…”
Section: Discussionsupporting
confidence: 84%
“…Banning (2010) [44] reported that predation could be extremely beneficial for bacteria living in oligotrophic marine environments, and marine Actinobacteria were shown to be highly metabolically active [45,46]. Morocco, because of its specific geographic position, bears a unique marine environment characterized by important temperature variations throughout the year [47].…”
Section: Introductionmentioning
confidence: 99%
“…The cell-tocell contact between the epibiotic predator and its prey is crucial for the transfer of compounds between their cells (Castelle and Banfield, 2018;Yakimov et al, 2022). As a consequence of the limited literature on culture-based investigations, our current state of understanding of the behavior of epibiotic lifestyles is relatively poor (Bor et al, 2020;Batinovic et al, 2021;Yakimov et al, 2022). However, Cross et al (2019) suggested that to clearly demonstrate cell-tocell contact, conditions that could enhance predator abundance to the degree that allows detailed microscopic characterization must be evaluated.…”
Section: Mechanisms Of Predation By Bacteria and Actinomycetota Speciesmentioning
confidence: 99%